2013
DOI: 10.1107/s1744309113011937
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray analysis of the flagellar motor `brake' molecule YcgR with c-di-GMP fromEscherichia coli

Abstract: In Escherichia coli and Salmonella enterica, bis-(3 0 -5 0 )-cyclic dimeric guanosine monophosphate (c-di-GMP), a ubiquitous bacterial second-messenger molecule that participates in many cellular processes, can regulate flagellar motor speed and reduce cell swimming velocity by binding to the PilZ-containing protein YcgR. Here, the crystallization and preliminary X-ray crystallographic analysis of YcgR with c-di-GMP are reported. The crystals diffracted to 2.3 Å resolution and belonged to space group R3:H, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2B). PDE domain dimers have been previously identified (Table S2) [15–17,19,37,38]. PDE dimerisation involving PDE‐α6 and the R helix has implications for active site formation.…”
Section: Resultsmentioning
confidence: 99%
“…2B). PDE domain dimers have been previously identified (Table S2) [15–17,19,37,38]. PDE dimerisation involving PDE‐α6 and the R helix has implications for active site formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies identifying direct interactions between diguanylate cyclases and motility machinery suggested that Pcc GCS regulation of O 2 -dependent motility could be due to protein–protein interactions with motility-related proteins in the same operon. Therefore, interactions between Pcc GCS and other P. carotovorum proteins were identified by affinity pull-down assays followed by mass spectrometry analysis.…”
Section: Resultsmentioning
confidence: 99%
“…C-di-GMP regulates swimming motility through a transcription factor FleQ which actives the transcription of genes involved in the biosynthesis of flagellum (Baraquet and Harwood, 2013). C-di-GMP can also directly bind with YcgR, which functions as a brake of flagellum to inhibit the rotation of flagellum (Paul et al, 2010) (Hou et al, 2013). A recent report has shown that c-di-GMP can also bind with ATPase FliI, a component of flagellar export apparatus (Trampari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%